Strategi Word of Mouth UMKM Tumpang Mbak Painem untuk Brand Awareness - Mardiyana, Dienesti Aurelia; Huwae, George Nicholas (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
The culinary business competition in Salatiga City has become increasingly intense, particularly among micro, small, and medium enterprises (MSMEs) offering similar products. The digital shift in consumer behavior requires business owners to adapt to modern marketing communication strategies. However, some traditional MSMEs still rely on conventional promotion methods, including Tumpang Mbak Painem, which sustains its business through Word of Mouth (WOM). This study aims to analyze the effectiveness of WOM in building brand awareness. The research employs a descriptive qualitative approach through in-depth interviews, observation, and documentation. The findings reveal that WOM plays a crucial role in introducing and strengthening the brand image through personal recommendations, customer testimonials, and the sharing of positive experiences. Moreover, online reviews on Google Review enhance consumer trust and indicate a transition toward a hybrid WOM model—combining offline and online communication. The brand awareness level of Tumpang Mbak Painem falls within the brand recall category, meaning consumers can remember the brand without external stimuli. Developing a hybrid WOM strategy is recommended to expand brand reach in the digital era.